Analysis of TJ-II experimental data with neoclassical formulations of the radial electric field. (10th September 2015) - Gutiérrez-Tapia, C; Martinell, J J; López-Bruna, D; Melnikov, A V; Eliseev, L; Rodríguez, C; Ochando, M A; Castejón, F; García, J; van Milligen, B P; Fontdecaba, J M
Abstract: Neoclassical theory provides usable expressions for studying transport in toroidal plasmas and computing the associated radial electric field. An algebraic and three semi-analytical models are used here to study the radial electric field in TJ-II plasmas and compare it with experimental data from a heavy ion beam probe (HIBP) and with DKES calculations. Good qualitative agreement as well as reasonable quantitative agreement is found which allows us to validate the models for describing TJ-II radial electric fields. Furthermore, a simple algebraic formulation (2005 Plasma Phys. Rep .31 14) provides physical insight for the interpretation of experimental data from the TJ-II heliac in spite of its complicated geometry, like the place of the transition from the electron to the ion root of the radial electric field, which occurs at the maximum value of collisionality, for example.